Lead structures for applications in photodynamic therapy. 5. Synthesis and biological evaluation of water soluble phosphorus (V) 5,10,15,20-tetraalkylporphyrins for PDT. - SENGE, MATHIAS; RYAN, AOIFE (My University, 2014)
Summary Improved photosensitizers for use in photomedicine must possess good water-solubility and optimal photophysical properties. Phosphorus(V) porphyrins fulfill these criteria and are a class of porphyrins with significant potential applications in phototherapy. Five phosphorus(V) porphyrins bearing alkyl substituents have been synthesized. Reasonable to good yields were obtained for all P(V) insertions and all compounds underwent biological evaluation for their PDT activity on two esophageal cancer cell lines, OE33 and SKGT-4. Their cellular uptake was investigated using a high content screening method. Notably, three compounds displayed good uptake and using the MTS cell proliferation assay, two were shown to have photocytotoxicity comparable to mTHPC (Temoporfin®) with IC50 values of 6.5 and 5.5 μM.
PUBLISHED
Keywords: Photodynamic therapy; Photosensitizers; Phosphorous; Porphyrins; Cancer; Esophageal cancer; Photodynamic therapy; Photosensitizers; Phosphorous; Porphyrins; Cancer; Esophageal cancer